Mathematics
nyasiareeves
2021-05-18 13:10:21
Product is 20 the sum is -12
ANSWERS
ShantellDukelow978
2021-05-18 13:53:21

Let one number be x Let another number be y ATQ x + y = -12 => y = -x -12 {mark as the first  equation} xy = 20 { mark as the second equation}  Substituting value of y in second equation x( -x - 12) = 20 -x² - 12x = 20 -x² - 12x - 20 = 0 { middle  term splitting} -x² -10x - 2x -20 = 0 -x( x + 10 ) -2 ( x +10 )  ( -x - 2 ) ( x + 10 ) are the factors.  -x -2 = 0                  x + 10 = 0  -x = 2                        x = -10 x = -2     so we get two values of x i.e. -2 and -10  now substituting value of x in first equation ( x = -2 )  y = -x - 12                    y = -x - 12  y = - ( -2 ) - 12             y = -(-10) - 12  y = 2 - 12                     y = 10 - 12  y = -10                         y = -2 So we  get to know that if x = -2 then y = -10 And when x = -10 then y = -10. Hope this help  :)

ADD ANSWER